The influence of pharmacist-led collaborative care on clinical outcomes in type 2 diabetes mellitus: a multicenter randomized control trial - Iqbal, Muhammad Zahid; Alqahtani, Saad Saeed; Mubarak, Naeem; Shahid, Sara; Mohammed, Rafiuddin; Mustafa, Abid; Khan, Amer Hayat; Iqbal, Muhammad Shahid (Frontiers in Public Health, 2024)
Background Health care providers are mandated to deliver specialized care for the treatment and control of type 2 diabetes mellitus. In Malaysia, Diabetes Medication Therapy Adherence Clinics (DMTAC) in tertiary hospitals have designated pharmacists to administer these services. Objective To assess the effects of pharmacist-led interventions within DMTAC on the outcomes of patients with type 2 diabetes mellitus in two distinct hospitals in Kedah, Malaysia. Methods Patients with type 2 diabetes were randomly selected from the two hospitals included in this study. The study population was divided into two equal groups. The control group consisted of 200 patients receiving routine care from the hospitals. On the other hand, the intervention group included those patients with type 2 diabetes (200), who received separate counseling sessions from pharmacists in the DMTAC departments along with the usual treatment. The study lasted 1 year, during which both study groups participated in two distinct visits. Results Parametric data were analyzed by a paired t-test and one-way ANOVA, while non-parametric data were analyzed by a Chi-squared test using SPSS v24. A p < 0.05 was considered statistically significant. The study presented the results of a greater reduction in HBA1c levels in the intervention group compared to the control group, i.e., 3.59 and 2.17% (p < 0.001). Moreover, the Systolic and Diastolic values of BP were also significantly reduced in the intervention group, i.e., 9.29 mmHg/7.58 mmHg (p < 0.005). Furthermore, cholesterol levels were significantly improved in patients in the intervention group, i.e., 0.87 mmol/L (p < 0.001). Conclusion Based on the findings of the current study it has been proven that the involvement of pharmacists leads to improved control of diabetes mellitus. Therefore, it is recommended that the government initiate DMTAC services in both private and government hospitals and clinics throughout Malaysia. Furthermore, future studies should assess the impact of pharmacist interventions on other chronic conditions, including but not limited to asthma, arthritis, cancer, Alzheimer’s disease, and dementia.